The role of permit relaxation policy in boosting micro-small business income during the COVID-19 - Syafrizal Syafrizal; Sartika Djamaluddin (Journal of Enterprise and Development (JED), 2023)
Purpose — This study investigates the effect of permit relaxation policy on micro and small businesses income by considering other factors, such as business capital, labor, business area, business sector, location ownership and business facilities.Method — This study employs quantitative methods by analyzing panel data related to the application for micro and small business permits, specifically focusing on the relaxation program, which was administered by the Department for Investment and Integrated One Stop Services of the Jakarta Capital City Government. The data covers the period from 2020 to 2022 and encompasses all areas, including five cities and one regency, with permits issued by 267 Service Units in Jakarta.Result — The findings of this study, derived from regression analysis and bivariate analysis, reveal a notable positive impact of business permits obtained through the relaxation program on the increase in business income. Specifically, businesses that obtained permits from the relaxation program experienced a higher income of 5.27% compared to those without permits. Furthermore, factors such as capital, labor, and the business sector collectively contribute to a significant positive effect on enhancing business income.Contribution — This research contributes to the existing literature by addressing the gap in previous studies that have not examined the impact of permit relaxation policy on the income of micro and small businesses. It offers valuable insights and knowledge to enhance understanding in this area of study.